COMPARISON OF LUMBAR DRAIN INSERTION AND CONSERVATIVE MANAGEMENT IN THE TREATMENT OF TRAUMATIC CSF RHINORRHOEA - Khan, Riffatullah; Sajjad, Muhammad; Khan, Abdul Aziz; Ahmad, Bilal; Ahmad, Sohail; Mushtaq, Muhammad; Sultan, Saad; Iftikhar, Osama; Shah, Syed Faizan Hassan (Journal of Ayub Medical College Abbottabad, 2019)
Background: Conservative management of traumatic CSF rhinorrhoea is associated with a greater risk of developing meningitis in the presence of active CSF leak. Lumbar drains have been reported to be better than conservative management alone in stopping CSF leaks following traumatic brain injury. Methods: This randomized controlled trial enrolled 60 patients with CSF rhinorrhoea and divided them into two groups. One group was managed with conservative management plus a lumbar drain (group A) and the other was managed with conservative management alone (Group B). Length of CSF rhinorrhoea in days was estimated in both groups. Results: There was a statistically significant difference in in mean length of CSF rhinorrhoea in both groups. In group A, mean Length of CSF rhinorrhoea was found to be 3.4 days ±1.1 SD, while in group B it was 6.75 days ±1.96 SD (p=0.001). Stratification with respect to gender, age, duration and type of trauma showed similar trend (p<0.05 in all cases). Conclusions: Patients who underwent lumbar drain insertion plus conservative management demonstrated significantly shorter length of CSF rhinorrhoea when compared to conservative management alone in the treatment of traumatic CSF rhinorrhoea. Keywords: CSF rhinorrhoea; Traumatic brain injury; Lumbar drain; conservative management, Cerebrospinal Fluid